Design and development of an autonomous sumo robot - Alfredo Setiabudi (2009)
This project is to design and develop an autonomous sumo robot. An autonomous sumo robot is able to have a match with another sumo robot, where it is supposed to automatically defend any attack performed by the opponent and trying to push the opponent out of the arena. The developed robot is expected to participate in Singapore Robotic Games 2009, an annual competition for robots from all over Singapore. There are three main stages in the design and development process of the sumo robot. The first stage is the concept and detailed design development. The objective of this stage is to select the best possible design that has the greatest chance to win in a match. The second stage is the fabrication stage. In this stage, every part of the robot is to be fabricated as planned previously. In this project, every single part, either mechanical part of electronic part, of the robot is fabricated by the author independently. Then, the final stage is to test the sumo robot and do necessary improvements to make sure that it can perform the intended tasks well. Based on the author’s observation on the existing sumo robots, there are two types of them. They are high-speed type and high-torque type. The wedge of high-speed type sumo robot is the most crucial part. Once the opponent’s wedge gets under its wedge, it would surely lose its stability and be pushed away easily. In addition, high speed processor is necessary to cope with the robot’s movement speed. On the other hand, high-torque type depends on the quality of its drive system. High quality motors and wheels or tracks are necessary. Since this project has limited resources, the author decided to build a hybrid sumo robot, where the motor and processor quality are not that critical. The concept is to build a robot with moderate-speed movement so that it could avoid opponent’s attacks and do counter-attacks from the weak sides of the opponent.